Manufacturing thick laminates using a layer by layer curing approach - Sun, Xiaochuan; Cook, Lawrence; Belnoue, Jonathan P-H.; Tifkitsis, Kostas I.; Kratz, James; Skordos, Alexandros A. (Elsevier, 2024)
The work presented in this paper puts forward a manufacturing strategy for the processing of thermosetting composites based on Layer by Layer (LbL) curing. The process operates additively with sublaminates placed in a heated press, partially cured while consolidating, followed by loading of the next sublaminate and repeating the cycle until part completion. Coupled consolidation-cure simulation was utilised to design the process and establish its capabilities showing that halving the cure time is possible for thick parts. Mechanical testing showed that for pre-cure of placed layers below the gelation degree of cure, interlaminar properties are equivalent to those of conventionally manufactured material. A trial was carried out demonstrating successfully the LbL process. On-line measurements of temperature and compaction matched the predictions of the simulation, whilst the quality of the material produced is equivalent to that of conventionally produced composites.
Keywords: Materials; 4016 Materials engineering; 4017 Mechanical engineering